Co-produced decentralised surveys as a trustworthy vector to put employees’ well-being at the core of companies’ performance - De Boisanger, Adèle Bréart; Sims-Schouten, Wendy; Sicard, Francois (Frontiers in Blockchain, 2025)
Assessing employees’ wellbeing has become central to fostering an environment where employees can thrive and contribute to companies’ adaptability and competitiveness in the market. Traditional methods for assessing wellbeing often face significant challenges, with a major issue being the lack of trust and confidence employees may have in these processes. Employees may hesitate to provide honest feedback due to concerns not only about data integrity and confidentiality, but also about power imbalances among stakeholders.In this context, blockchain-based decentralised surveys, leveraging the immutability, transparency, and pseudo-anonymity of blockchain technology, offer significant improvements in aligning responsive actions with employees’ feedback securely and transparently. Nevertheless, their implementation raises complex issues regarding the balance between trust and confidence. While blockchain can function as a confidence machine for data processing and management, it does not inherently address the equally important cultural element of trust. To effectively integrate blockchain technology into wellbeing assessments, decentralised wellbeing surveys must be supported by cultural practices that build and sustain trust. Drawing on blockchain technology and relational cultural theory, we explain how trust-building can be achieved through the co-production of decentralised wellbeing surveys, which helps address power imbalances between the implementation team and stakeholders. Our goal is to provide a dual cultural-technological framework along with conceptual clarity on how the technological implementation of confidence can connect with the cultural development of trust, ensuring that blockchain-based decentralised wellbeing surveys are not only secure and reliable but also perceived as trustworthy vector to improve workplace conditions.